Clinical research in the medical colleges of U.S. Universities: innovation trends - Kulichenko, Alla; Boichenko, Maryna; Куліченко, Алла Костянтинівна; Бойченко, Марина; Куличенко, Алла; Бойченко, Марина (Суми: СумДПУ ім. А. С. Макаренка, 2020)
The article reveals innovation trends and their features during clinical trials in medical colleges of U.S. universities. The authors have found that clinical research deals with developing and implementing innovative products, tools, technologies, and equipment for quality medical care, treatment, and disease prevention. Clinical research focuses on observational studies and clinical trials. Note that in clinical trials global innovation trends include patient-centeredness; ensuring the protection of information within e-health; development of mobile healthcare technologies; automation of materials for clinical trials; cybersecurity priority.
Клінічні дослідження в діяльності медичних коледжів університетів США: інноваційні тенденції
Клинические исследования в деятельности медицинских колледжей университетов США: инновационные тенденции
Keywords: American medical colleges; medical education; research; innovation trends; features; observational studies; clinical research; clinical trials; американські медичні коледжі; медична освіта; дослідження; інноваційні тенденції; особливості; клінічні дослідження; обсерваційні дослідження; клінічні випробування; американские медицинские колледжи; медицинское образование; исследование; инновационные тенденции; особенности; клинические исследования; обсервационные исследования; клинические испытания